2018
DOI: 10.3390/foods7120194
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Eucalyptus, Chestnut and Heather Honeys from Portugal Using Multi-Parameter Analysis and Chemo-Calculus

Abstract: The present study was conducted to evaluate the quality and bio-functional properties of Portuguese honeys of different botanical and geographical origins. Quality parameter analyses included the determination of palynological (predominant, secondary, minor and isolated pollen percentage), physicochemical (°Brix, moisture content, pH, electrical conductivity, free acidity, total dissolved solids, salinity, vitamin C content and specific weight) including colour-metrics (CIELAB, Pfund and colour intensity deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
53
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 40 publications
18
53
3
2
Order By: Relevance
“…In the present study, all samples had a percentage of moisture content below the imposed limit of ≤20%, the maximum acceptable moisture content of honey by the European Community Directive (Ministry of Agriculture, Rural Development and Fisheries, ; Codex Alimentarius, ). The results presented herein are in accordance with those of other works (Can et al., ; Estevinho et al., ; Karabagias et al., ; Silva et al., , ; Zhou et al., ).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, all samples had a percentage of moisture content below the imposed limit of ≤20%, the maximum acceptable moisture content of honey by the European Community Directive (Ministry of Agriculture, Rural Development and Fisheries, ; Codex Alimentarius, ). The results presented herein are in accordance with those of other works (Can et al., ; Estevinho et al., ; Karabagias et al., ; Silva et al., , ; Zhou et al., ).…”
Section: Resultssupporting
confidence: 94%
“…All samples are below the maximum limit allowed (800 µs/cm) by Portuguese and European legislation (Ministry of Agriculture, Rural Development and Fisheries, ; Codex Alimentarius, ). These values are similar to those found in other studies (Belay et al., ; Karabagias et al., ; Louppis, Karabagias, Kontakos, Kontominas, & Papastephanou, ; Mondragón‐Cortez et al., ; Silva et al., ; Zhou et al., ). Several works reported that a linear relationship exists between the ash content and the electrical conductivity (Buba et al., ; Mondragón‐Cortez et al., ; Silva et al., , ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations